Regional Distribution and Relative Abundance of Serotonin2c Receptors in Human Brain: Effect of Suicide - Pandey, Ghanshyam N.; Dwivedi, Yogesh; Ren, Xinguo; Rizavi, Hooriyah S.; Faludi, Gabor; Sarosi, Andrea; Palkovits, Miklos (Neurochemical research, 2006)
Abnormalities in serotonin receptor subtypes have been observed in the postmortem brain of suicide victims. We examined the regional distribution of serotonin (5HT)2C receptor mRNA in several areas of the human brain and also compared its protein and mRNA expression in the prefrontal cortex (PFC), hippocampus, and choroid plexus between suicide victims and normal control subjects. 5HT2C receptors were found to be distributed in several areas of the human brain (in order of abundance): highly concentrated and richest in choroid plexus; hypothalamus; nucleus accumbens; with the lowest abundance in PFC and cerebellum. Comparison of 5HT2C receptors between suicide victims and control subjects showed higher protein levels in the PFC but not the hippocampus or choroid plexus of suicide victims. However, there were no significant differences in mRNA levels between suicide victims and control subjects in these brain areas. These results suggest that 5HT2C receptors are richly distributed throughout the brain with the highest level in the choroid plexus and that abnormalities in protein expression of 5HT2C receptors in the PFC may be associated with suicide.